2011
DOI: 10.1007/s11914-011-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bone Marrow and Visceral Fat on Bone Metabolism

Abstract: The protective effect of total fat mass on bone mineral density (BMD) has been challenged with studies showing no or negative association after adjusting for weight. Subsequently, more studies have evaluated the relationship of regional adiposity with BMD, and findings were inconsistent for central obesity. Advancements in imaging techniques enable us to directly and noninvasively study the role of adiposity on skeletal health. Visceral adiposity measured by computed tomography (CT) has consistently been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 49 publications
1
64
1
3
Order By: Relevance
“…Many low-grade inflammatory conditions are associated with low bone density, and inhibition of inflammation may protect against inflammation-induced bone loss [1][2][3][4]. Resveratrol (RSV) is a natural polyphenolic compound (3,5,4 0 -trihydroxy-trans-stilbene) present in, for example, nuts and the skin of grapes, where it protects the plants against pathogens and other external stressors of the plant [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many low-grade inflammatory conditions are associated with low bone density, and inhibition of inflammation may protect against inflammation-induced bone loss [1][2][3][4]. Resveratrol (RSV) is a natural polyphenolic compound (3,5,4 0 -trihydroxy-trans-stilbene) present in, for example, nuts and the skin of grapes, where it protects the plants against pathogens and other external stressors of the plant [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, no such association was found between overall adiposity and MAT 42 . Interestingly MAT is increased in patients with anorexia nervosa, characterized by extreme weight loss 43 , and MAT can recover to normal levels once weight is normalised 33 .…”
Section: <Figure 7 Near Here>mentioning
confidence: 74%
“…MAT was thought for a long time to be metabolically inert; however, recent studies have begun to reassess the role of fat cell in bone, with 1 H MRS playing an important role in this process [34][35][36][37][38][39][40][41][42][43] .…”
Section: Bone Marrowmentioning
confidence: 99%
“…BMD correlates with age and in the spine decreases by about 20% between 40 and 70 years (7,15) . Histomorphometric studies have shown that skeletal blood flow is correlated with output rate of osteoblasts (6,16,17,18) . Atherosclerosis causes endothelial dysfunction, which can reduce the release of endothelial nitric oxide synthase, limiting osteoblast formation or decreasing the anabolic effect of bone (19,20) .…”
Section: Discussionmentioning
confidence: 99%